Marketing Strategy Determination Using Markov Chain and Game Theory: A Case Study of Ready-to-Drink Tea Products - Herdiana, Mochamad Rafi; Dewi, Yulida Intani; Ikatrinasari, Zulfa Fitri; Amrina, Uly (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Decrease in the number of demand in the market and the transfer of consumers from the Nuu Green Tea brand to the Pucuk Harum Tea brand or vice versa is a result that can occur from market share competition. The calculation results obtained after doing manual calculations using the Markov chain method are the probability of transferring the subscription from each product a few times ago, at this time, and the time to come. For the time to come alone based on the steady state obtained is in the 10th year period. With the probability value of the movement from the shoot tea to Nuu Green Tea is 0.413 for a period some time ago and at this time, for other products transfer can be seen in Figure IV.6. For the value of the steady state in the 10th iteration with the mastery of the shoots of the market share of 0.4158 or 41.58% and Nuu Green Tea controlled the market share of 0.5841 or 58.41%. The calculation results that have been done manually and the use of application assistance can be concluded that the use of the maximin-minimax method produces an optimum solution, namely on X1 for row players (The Pucuk), and Y1 for column players (Nuu Green Tea). With a game value of 32. then the best marketing strategy used by Teh pucuk and Nuu Green Tea is the attribute 'flavor variant' by utilizing the flavor variant of the two can compete in the flavor variant.